Effects of metformin and statins on outcomes in men with castration-resistant metastatic prostate cancer: Secondary analysis of COU-AA-301 and COU-AA-302. (July 2022) - Wilson, Brooke E.; Armstrong, Andrew J.; de Bono, Johann; Sternberg, Cora N.; Ryan, Charles J.; Scher, Howard I.; Smith, Matthew R.; Rathkopf, Dana; Logothetis, Christopher J.; Chi, Kim N.; Jones, Robert J.; Saad, Fred; et al.
Abstract: Background: The associations of metformin and statins with overall survival (OS) and prostate specific antigen response rate (PSA-RR) in trials in metastatic castration-resistant prostate cancer remain unclear. Objective: To determine whether metformin or statins ± abiraterone acetate plus prednisone/prednisolone (AAP) influence OS and PSA-RR. Design, setting and participant: COU-AA-301 and COU-AA-302 patients were stratified by metformin and statin use. Cox proportional hazards models were used to estimate hazards ratio (HR) stratified by concomitant medications, and a random effects model was used to pool HR. We compared PSA-RR using Chi χ 2 test. Results: In COU-AA-301-AAP, metformin was associated with improved PSA-RR (41.1% versus 28.6%) but not prolonged OS. In COU-AA-301-placebo-P, there was no association between metformin and prolonged OS or PSA-RR. In COU-AA-302-AAP, metformin was associated with prolonged OS (adjHR 0.69, 95% CI 0.48–0.98) and improved PSA-RR (72.7% versus 60.0%). In COU-AA-302-P, metformin was associated with prolonged OS (adjHR 0.66, 95% CI 0.47–0.93). In pooled analysis, OS was prolonged among those treated with metformin (pooled HR 0.77, 95% CI 0.62–0.95).In COU-AA-301-AAP, statins were associated with an improved OS (adjHR 0.76, 95% CI 0.62–0.93), while there was no difference in COU-AA-301-P. There was no association with statins and OS in either COU-AA-302 groups. When pooling HR, OS was prolonged among those treated with statins (pooled HR 0.78, 95% CI 0.68–0.88). Conclusion: Within the limitations of post-hoc sub-analyses, metformin and statins are associated with a prolonged OS and increased PSA-RR, particularly in combination with AAP. Highlights: We examined the effect of metformin and statins on outcomes in registrational abiraterone acetate plus prednisone/prednisolone trials. Results were inconsistent across subgroups and trials with respect to prostate-specific antigen response rate and overall survival. Pooled analyses suggests prolonged overall survival with metformin or statins. These results need prospective evaluation in ongoing trials.